(untitled) (Research, Society and Development, 2020)
Brazil is among the ten countries with the highest number of suicide deaths in the world. The ability of academics in the health sector to early identify patients with suicidal ideation in their practice environments is promising and fundamental to prevent this phenomenon. This study aimed to investigate, through the validated questionnaire QUACS, the attitude and self-perception of training of medical students regarding suicidal behavior, as well as to determine associated factors. The sample consisted of students from the 6th and 8th periods of medicine from Minas Gerais State University (UEMG), Passos unit. This was an observational, cross-sectional study with a quantitative and qualitative approach. With the statistical evaluation of the results, we concluded that the medical students from 6th and 8th periods do not feel empowered to deal with suicidal behavior, possibly due to the gaps in their learning process that need to be detected and filled. Measures like the expansion of medical students’ contact with cases of suicidal behavior in practice environments can be promising in this scenario. As a limitation of this study, there is the fact that it was conducted at a single public university in the southern region of Minas Gerais. Therefore, there is a need to expand the sample to other universities, including private universities from Passos and other regions of the country.